HEALTH-SAVING TECHNOLOGIES IN THE ACTIVITY OF A SPECIALIST OF SOCIAL WORK AS A BASIS FOR PUBLIC HEALTH PROBLEM DECISION - Boldina, M.A. (Tambov University Review. Series: Humanities, 2016)
The concept “social technology” is analyzed, which is defined as an activity, as a result of which the goal is achieved, and the activity object is changed. It is determined that social activity as any social technology is diverse in its particular embodiment, the objective function, nature and results. Example is the use of health protection technologies in social work. Health saving technologies are seen as a set of pedagogical, psychological and medical effects, aimed at protecting and promoting the health and formation of value attitude to health. The analysis of the scientific literature has made it possible to identify that in the formation of a healthy way of life there are different social technologies working both with the different categories of clients and personnel of social agencies. In working with the personnel a wide range of measures to protect against adverse biological and social factors are used. Within the system of social protection, the most effective technologies are rehabilitation and social adaptation by means of physical culture and sports, as well as by adaptive physical education. In addition, the technology used in the system of social protection of the population, include major issues related with the life of people with limited mobility in modern society. It is proved that qualified assistance to clients in solving problems related to health, determines the level of preparation of the social worker at the appropriate medical expertise, who has a coordinating role and is involved in the provision of health and social care.